Integration of Palestinian Refugee Children from Syria in UNRWA Schools in Lebanon - Beydoun, Zahraa (J Int Migr Integr, 2021)
Following the Syrian conflict that began in 2011, Lebanon received more than one million refugees including 44,000 Palestinian refugees from Syria (PRS). PRS children were integrated into existing schools run by the United Nations Relief and Works Agency (UNRWA). Despite efforts by UNRWA to integrate the newly displaced into its services in Lebanon, only 58% of 6–18-year-old PRS children were enrolled in school in 2014. Informed by ecological systems theory, we examined the role of parental characteristics in determining school enrollment among PRS children following displacement into Lebanon. Utilizing data from the 2014 UNRWA Vulnerability Assessment (N = 12,378 6–18-year-old children), we specified crude and adjusted logistic regression models to predict child school non-enrollment including a set of variables on head of family characteristics (gender, age, education, and presence/absence of chronic disease) and post-displacement household characteristics (crowding, wealth, camp residence, region, and type of dwelling). The results show that, adjusting for household characteristics, a child living in a family whose head has secondary education or higher is more likely to be enrolled in school compared to one living in a family headed by someone with less than secondary education. Parental education remains the strongest predictor of child school enrollment despite displacement-related household disadvantage. To break the cycle of intergenerational educational disadvantage, it is critical for UNRWA to proactively design school retention programs for PRS children living in families whose head had limited access to education. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s12134-020-00793-y.